(untitled) (Italiano LinguaDue, 2023)
La lettura di un saggio può a volte non lasciare traccia nel lettore, il che non è mai un bel risultato. A volte invece stimola la nostra intelligenza, forse il saggio non ci ha convinto del tutto ma non riusciamo a liberarcene, perché ha toccato dei temi che riconosciamo importanti ma complessi, non facili da dipanare. Così può succedere che i dubbi o le domande – nel nostro caso sui confini tra frase e testo – che il saggio ha suscitato prendano forma scritta e vengano addirittura inviate all’autore del saggio. E capita che l’autore risponda. “Dear Michele”: reflections and questions in the form of a letter on the difficult boundaries between sentence and text Reading an essay may sometimes leave no trace in the reader, which is never a good thing. Sometimes, on the other hand, it stimulates our intelligence, perhaps the essay has not completely convinced us but we cannot get rid of it, because it has touched on topics that we recognise as important but complex, not easy to unravel. So it can happen that the doubts or questions – in our case about the boundaries between sentence and text – that the essay has raised take written form and are even sent to the author of the essay. And it happens that the author replies.